2024
DOI: 10.3390/buildings14051295
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Space Utilization in Skyscrapers Designed with Prismatic Form

Hüseyin Emre Ilgın,
Özlem Nur Aslantamer

Abstract: The enduring appeal of prismatic shapes, historically prevalent in office building designs, persists in contemporary skyscraper architecture, which is attributed particularly to their advantageous aspects concerning cost-efficiency and optimal space utilization. Space efficiency is a crucial factor in prismatic skyscraper design, carrying substantial implications for sustainability. However, the current academic literature lacks a complete exploration of space efficiency in supertall towers with prismatic form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The study found space efficiency ranging from 78% to 88%. Ilgın [25][26][27][34][35][36] investigated space efficiency in various types of skyscrapers, including office, residential, and mixed-use towers. Common findings across these studies included the frequent use of outriggered frame systems and a central core, and an inverse relationship between tower height and space efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The study found space efficiency ranging from 78% to 88%. Ilgın [25][26][27][34][35][36] investigated space efficiency in various types of skyscrapers, including office, residential, and mixed-use towers. Common findings across these studies included the frequent use of outriggered frame systems and a central core, and an inverse relationship between tower height and space efficiency.…”
Section: Introductionmentioning
confidence: 99%